ROLE OF Na+, K+, 2Cl– -COTRANSPORTER AND POTASSIUM CONDUCTIVITY IN THE REALIZATION OF THE EFFECT OF CARBON MONOXIDE, IN THE SMOOTH MUSCLE OF VISCERAL ORGANS - A. V. Skvortsov; M. A. Medvedev; V. B. Studnitsky; I. V. Kovalev; Y. A. Pogudin; S. V. Gusakova; O. I. Antonov; J. G. Birulina (Бюллетень сибирской медицины)
The aim of this study was to investigate the role of the Na+, K+, 2Cl– -transport and potassium conductance, in the implementation of the effects of carbon monoxide in the SMC taenia coli and ureter of guinea pig.Materials and methods. The study was conducted by the method of double saccharose bridge. Was studied the effects of carbon monoxide donor CORM2 in ureter and smooth muscle of guinea pig of taenia coli, in normal Krebs solution, against inhibitor-bumetanide and potassium channel blocker tetraethylammonium chloride (TEA). Studied the effects of bumetanide in normal Krebs solution and the background of TEA.Main results. CORM2 causes inhibition of contractile activity of SMC taenia coli and guinea pig ureter. Its effect is weakened by bumetanide and TEA. Bumetanide causes inhibition of contractile activity of SMC taenia coli, and its effect is weakened by TEA.Conclusions. In this way, it shows that there are tissue-specific mechanisms of interrelation effects CO and ion conductivity.